Students' Metacognitive Regulation in Mathematical Modeling Based on Gender - Ely Aulia Haq; Abadi; Janet Trineke Manoy (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2025)
Metacognitive regulation is a crucial skill in mathematics learning as it plays a significant role in managing cognitive processes during problem-solving. This study aims to explore students’ patterns of metacognitive regulation in mathematical modeling based on masculine and feminine gender characteristics. The focus is directed toward how students plan, monitor, and evaluate their thinking while solving contextual problems related to systems of linear equations in two variables. This research employs a qualitative descriptive approach. The participants were purposively selected based on their psychological gender characteristics and equivalent mathematical abilities. Data were collected through questionnaires, tests, mathematical modeling tasks, and semi-structured interviews, then analyzed according to the stages of mathematical modeling. The findings reveal that the masculine male student demonstrated efficient metacognitive regulation strategies, with a focus on procedural accuracy and selective internal monitoring. He simplified the modeling process without sacrificing accuracy and showed confidence in validating his solutions. In contrast, the feminine female student exhibited reflective and comprehensive regulation patterns, with a strong focus on contextual understanding and layered validation processes. She constructed models systematically and performed repeated checks on alternative solutions. These findings highlight that gender characteristics contribute to differences in students’ metacognitive strategies during mathematical modeling. The results are expected to inform the development of instructional practices that are more responsive to students’ diverse cognitive approaches.